Corporate life and death: who succumbs, who survives during disruption?. Issue 6 (30th October 2018) - Blitz, Amy
Abstract : Purpose: This paper provides a disruption survival guide for companies during times of macro transformation. Design/methodology/approach: The research compared the S&P 500 – as proxy for the US economy – from 1996 and 2018. Of companies no longer on the list, 12 died, including two from manufacturing: Bethlehem Steel and Outboard Marine Corporation (OMC). Still, some US manufacturers survived or even thrived during the period. To understand why, the paper compares Bethlehem, which died in 2003, to US Steel, which has survived but was removed from the S&P 500 list in 2014, and to Nucor, which has stayed on the list. POSCO is also used for comparison. The OMC case adds a different industry perspective. Findings: The main findings from these cases are as follows: stay fit financially and avoid overreaching in good times, use operation strategies such as Lean and Six Sigma to build a culture of continual innovation and stay close to customers to compete on the basis of differentiation, particularly if competing on price is not a realistic option. The good news is differentiation is possible even in seemingly commoditized sectors like steel. Research limitations/implications: This paper contributes to the literature on differentiation as a strategy for competing with low-cost disruptors. Practical implications: This paper provides insights into the use of Lean, Six Sigma and other strategies for creating a culture of continual innovation among employees, customers, suppliers and other strategic partners. And, building on this culture, to compete on the basis of value-added differentiation, particularly if competing on price is not a realistic option. Originality/value: The paper cuts through complex, fast-changing, transformative macro issues – e.g., Chinese competition and trade uncertainties related to new tariffs – and provides practical, timeless insights for navigating in such times. The focus here is on strategies for competing on the basis of value-added differentiation, particularly if competing on price is not a viable option. The good news is such competition is possible even in seemingly commoditized sectors like steel.